RELEVANSI NILAI ADAB DAN TAKZIM DALAM KITAB TA’LIM AL-MUTA’ALLIM TERHADAP CAPAIAN KEBERKAHAN ILMU DI ERA MODERN - Muhamad Faiz Nurfalahi; Muhammad Husni (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the relevance of the values of manners (adab) and respect (takzim) in the book Ta’lim al-Muta’allim by Imam Az-Zarnuji to the concept of the blessings of knowledge in the context of contemporary Islamic education. Amid the modernization of education, which tends to emphasize cognitive and pragmatic aspects, the spiritual dimension in the form of the blessings of knowledge has become increasingly marginalized. This study uses a qualitative approach through library research with content analysis techniques on the text of Ta’lim al-Muta’allim and relevant supporting literature. The results of the study indicate that manners and respect from Az-Zarnuji’s perspective are not merely social ethics, but fundamental prerequisites for achieving the blessings of knowledge. These blessings manifest through sincerity of intention, respect for teachers, and the honoring of knowledge and books. These values remain relevant and applicable in modern education as a foundation for shaping students’ character